Mathematical Resilience as a Conceptual Framework for School Practice - URSZULA OSZWA (Ignatianum University Press, 2022)
The aim of the study is to analyze mathematical resilience from theoretical and practical perspectives. The paper is based on a review of the literature. Research on mathematics education has revealed a large proportion of students with math anxiety whose achievements in math are worsening. Such results encourage a discussion on preventing math anxiety. Research on the resilience of children and adolescents has accelerated in recent decades, resulting in the formulation of the concepts of school and mathematical resilience. The article presents the ecological model of mathematical resilience. The role of parents and teachers in promoting mathematical resilience is also described. The paper presents areas where students can self-foster mathematical resilience. The conclusions are related to the importance of strengthening mathematical resilience in education.